Stock Market Interdependence, Contagion, the Financial Subprime Crisis and the European Sovereign Debt Crisis: Evidence from the Chinese’s Stock Market - Jayech, Selma; Mazigh, Lamia Jaidane; Abdennadher, Emna (Asian Academy of Management Journal of Accounting and Finance, 2022)
This study analyses the contagion effects of the American, the British and the Greek stock markets on the Chinese stock market in the context of the 2007–2010 American and European financial crises. Two contagion tests have been performed using the Archimedean copula functions. The results of the first test suggest that the financial contagion existed between UK/China in the 2007 subprime financial crisis period and between U.S./China and U.K./China in the 2010 European sovereign debt crisis period. Finally, the second test shows that the contagion effects of the 2010 European sovereign debt crisis were clearly more intense than those caused by the 2007 subprime financial crisis just for the U.S./China pair. Investors' sentiment and behavior indirectly have impact on financial risk contagion in Chinese stock markets.